Transformasi Bisnis Komoditas Cabai di NTB: Analisis Disparitas Pertumbuhan Cabai Merah dan Cabai Rawit 2013–2022 - Leni Yupita Rizki; Nabila Silvana; Tiara Nabila Huda; Karina Juniarti Utami; Herie Saksono (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2024)
Chili is a strategic horticultural commodity with high economic value in the Indonesian economy. This longitudinal study analyzes the dynamics of chili business growth in West Nusa Tenggara Province during the 2013-2022 period, focusing on growth disparities between red chili and cayenne pepper. Although many studies have examined chili farming from various aspects, there is a literature gap in analyzing comparative long-term growth performance between the two chili varieties, particularly in NTB. The main problem is the unclear growth patterns differentiating the two commodities, which hinders the development of appropriate business strategies. This research aims to analyze the growth dynamics of both commodities and formulate strategic implications for sustainable chili agribusiness development. Using a quantitative approach with a longitudinal design based on time series data from "One Data NTB," the analysis was conducted using Compound Annual Growth Rate (CAGR) to measure growth rates over a decade. The results show significant growth disparities, where red chili demonstrates comprehensive expansion (CAGR of harvested area 9.979% and production 14.771%), while cayenne pepper experiences contraction in harvested area (-1.513%) but records higher productivity growth (5.731%). These different patterns reflect a strategic reorientation in the chili business in NTB, with a transformation of cultivation preferences from cayenne pepper to red chili driven by economic factors and market integration. The proposed recommendations include developing differentiated incentive systems, strengthening supply chain institutions, investing in research and innovation, implementing diversification and risk mitigation strategies, and developing capacity and knowledge management that will support the sustainability of chili agribusiness in NTB.